2021
DOI: 10.21203/rs.3.rs-786571/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mislocalisation of Pax7 and Its Interaction with Importin-α1 (KPNA2) in Dystrophin-Deficient Myoblasts

Abstract: Background: Pax 7 is one of the key factors in the development of tissues and organs during embryogenesis. It has been suggested that Pax7 may play a major role during myogenesis. Our previous study has shown that Pax7 cell is attenuated in the mdx embryo during gestation as well as in dystrophic muscle indicating that an absence of dystrophin in muscle affects pax7 regulation in Duchene Muscular Dystrophy (DMD). Therefore, we aimed to investigate the Pax7 expression pattern as well as their specific transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Pax7 is a transcription factor known to be indispensable in myogenesis by modulating MyoD expression and maintaining healthy and mature cell differentiation [15,16]. Pax7 belongs to the highly conserved paired-box (Pax) gene family transcription factor and is critically expressed during the development of the nervous and muscular systems [17]. Interestingly, it has been revealed that overexpression of Pax7 regulates myogenic differentiation by downregulating MyoD expression and prevents MyoG induction in fetal Duchenne Muscular Dystrophy (DMD) muscle tissues, suggesting a delay in myofibers differentiation program [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Pax7 is a transcription factor known to be indispensable in myogenesis by modulating MyoD expression and maintaining healthy and mature cell differentiation [15,16]. Pax7 belongs to the highly conserved paired-box (Pax) gene family transcription factor and is critically expressed during the development of the nervous and muscular systems [17]. Interestingly, it has been revealed that overexpression of Pax7 regulates myogenic differentiation by downregulating MyoD expression and prevents MyoG induction in fetal Duchenne Muscular Dystrophy (DMD) muscle tissues, suggesting a delay in myofibers differentiation program [18,19].…”
Section: Introductionmentioning
confidence: 99%